Ratings of Attention Problems in ADHD: A Continuum - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2009)
To determine whether ADHD should be classified in three distinct DSM-IV diagnostic subtypes or a continuum of attention problems, maternal ratings of attention on the Child Behavior Check List (CBCL), in Durch boys at age 7, 10, and 12 years, were fitted to class models, assuming either subtype or severity differences.